Uji Kinerja Mesin Perajang Singkong Menggunakan Mekanisme Pengumpan Otomatis - Mantutu, Anggi R.; Mangesa, Daud P.; Tobe, Adi Yermia (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2024)
This research focuses on testing the performance of the cassava chopper machine using an automatic feeder mechanism that is applied to the cassava chopper machine to speed up the production process and improve product quality. The purpose of this research wants knowing the working principle of the cassava chopper using an automatic feeder, knowing the performance capacity of the cassava chopper using an automatic feeder, knowing the percentage of damage to the chopper and the value of the thickness of the chopper at one time of the chopping process. The research method used is a type of engine performance testing. Namely observing, measuring and calculating the performance testing of the cassava chopper machine. In collecting data for the calculation of chopping capacity and thickness of the sliced product, it was carried out by preparing 9 kg of cassava and the test was carried out 9 times using variations in the angle of the blade and 1 minute for each test. From the test results, it was found that the chopping capacity at blade setting A was 55.68 kg/hour, knife B was 57.48 kg/hour, and knife C was 59.34 kg/hour, with a slice thickness of 1-3mm.